THE IDEOLOGIZATION OF CALIPHATE HADITHS: TEXTUAL CRITICISM AND POLITICAL AUTHORITY IN CONTEMPORARY ISLAM - irpan saputra; Rasyid Alhafizh (Makkah: Journal Of Islamic Studies, 2025)
This study examines the ideologization of caliphate-related hadiths in contemporary Islamic political discourse and its implications for the construction of political legitimacy. It argues that the central challenge does not lie in the authenticity of the hadith corpus, but in the interpretive frameworks through which these narrations are selectively appropriated and mobilized. Employing a qualitative library-based research design, the study integrates classical hadith methodology with contemporary political analysis. Primary data consist of hadiths on leadership, obedience, and political authority drawn from major Sunni canonical collections, while secondary sources include classical commentaries and modern scholarship on political Islam. Through sanad evaluation, matan criticism, and critical discourse analysis, the research demonstrates that many caliphate-related hadiths, although textually authentic, were articulated within specific historical contexts and primarily convey ethical guidance rather than prescriptive political models. The findings reveal that contemporary ideological readings tend to absolutize selected narrations, marginalize ethical constraints, and conflate textual authenticity with political obligation. This interpretive reduction transforms hadith into instruments of political domination. The study concludes by proposing a methodological repositioning of hadith between ethics and power, reaffirming the Prophetic tradition as a moral framework that guides and constrains political authority rather than legitimizing immutable political forms.